Penerapan Pendekatan Konseling Eksistensial Humanistik untuk Mengurangi Perilaku Hedonis Siswa di SMAN 10 Makassar - Qawiyyan Fitri; Alimuddin Mahmud; Abdul Saman (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
This research was intended for reducing student hedonic behaved, using experiment type Pre-Experimental Design with research One-Group Pretest-Posttest Designs. Data was collected using questionnares and observation instruments. Data analysis used descriptive statistical analysis and non parametric inferential statistical analysis. The results of research showed that the hedonist behavior of the students before being given the treatment of existential humanistic counseling approached was in the high category and after being given the treatment of humanistic existential counseling is in the low category, the treatment was be given through three steps namely preliminary step, mid step and termination step with seven times for face-to-face meetings.